Motivasi Siswa Sekolah Dasar dalam Mempelajari Bahasa Arab Tinjauan Psikologi Belajar Anak - Nur Muh Muhammad (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2018)
Abstract: Student’s motivation in learning arabic language in children learn psichology review. Muhammadiyah Pakem Elmentary School is one of school use Arabic Language in his curriculum from class 1 to class 6.The students in Elmentary School have unique characteristics of the Scondary school or senior high school, because in Elmentary School will be end the children age. Therefore is very importen to know what motivasion a characteristics in this age.The aim of this research is to know the best method or tehnique in learning by knowing Student’s motivasion. This research use the qualitative method in data analizing.The result this research is motivasion from other is 72,2% (ekstrisik) and motivasion from inerself students’s is 16%. And the stay away factor the students as there is no preparation by students to learn and the dificult level material arabic language for the students.Keywords: student’s motivation, arabic learning, psichology